Manipulating Charge‐Transfer Kinetics of Lithium‐Rich Layered Oxide Cathodes in Halide All‐Solid‐State Batteries (Adv. Mater. 5/2023). Issue 5 (2nd February 2023) - Yu, Ruizhi; Wang, Changhong; Duan, Hui; Jiang, Ming; Zhang, Anbang; Fraser, Adam; Zuo, Jiaxuan; Wu, Yanlong; Sun, Yipeng; Zhao, Yang; Liang, Jianwen; Fu, Jiamin; et al.
Abstract : All‐Solid‐State Batteries The application of a lithium‐rich layered oxide (LLO) cathode in all‐solid‐state batteries (ASSBs) has been hampered by its low electronic conductivity and the high reactivity of its lattice oxygen. In article number 2207234, Ruizhi Yu, Jiantao Wang, Xifei Li, Chandra Veer Singh, Xueliang Sun, and co‐workers successfully address this by introducing an appropriate amount of conductive additives to the solid‐state electrodes and manipulating the surface chemistry, realizing long‐cycle‐life LLO‐based ASSBs.